Análises de filmes finos por power spectrum density e espectroscopia de força por AFM - Casagrande, Tainã Reges (2023)
In this work, thin films were produced using a misture of diketopyrrolopyrrole (DPP) and perylene diimide (PDI) based molecule, denoted as PDI-DPP-PDI, and poly [[4,8-bis [5-(2-ethylhexyl)-2-thienyl] benzo [1, 2-b:4,5-b′] dithiophene-2,6-diyl] [2-(2- ethyl-1-oxohexyl) thieno[3,4-b] thiophenediyl]] (PBDTTT-CT). These materials have complementary absorption spectra, being an essential feature for energy collecting in organic solar cells (OSCs). However, AFM images pointed to the presence of isolated and microsized PDI-DPP-PDI domains along the surface of the films, a feature that negatively impacts the performance of this blend in OSCs. Therefore, to improve the homogenization of the acceptor along the film, a pos-deposition treatment, denoted as solvent vapor annealing (SVA), was performed in a saturated atmosphere containing vapor of common organic solvents (chlorobenzene) for 3-10 minutes. This procedure changed morphology properties PBDTTT-CT:PDI-DPP-PDI active layer. Moreover, analyses carried out by power spectrum density (PDS) of images acquired from SVA treated film indicated that in the region of larger frequencies, across the length scale around 100 nm, it appears an additional fractal region with Ds of 0.95, indicating a flattened region, possibly related with changes in the PDI-DPP-PDI conformation after SVA treatment. This indicates an improvement in the molecular packing, a feature not observed in the as cast film. The analyses by force curve spectroscopy pointed out increased adhesion force and adhesion energy in SVA-treated PBDTTT-CT:PDI-DPPPDI films; this feature enhances the interface interaction with the top electrodes, reflecting in improved charge extraction in the photovoltaic device.